Non-thermal processing techniques for sustainable food supply chains - Kaiser Younis; Kausar Jahan; Ovais Shafiq Qadri; Khwaja Osama; Owais Yousuf (Sustainable Futures)
This review examines the role of non-thermal food processing technologies in fostering sustainable food supply chains. Emphasizing energy conservation, carbon emission reduction, and circular economy principles, we investigate various non-thermal methods, their industrial applications, and societal impacts. Nonthermal technologies, including Pulsed Electric Fields, High Hydrostatic Pressure, Cold Atmospheric Plasma, and Light-Based Technologies, have been scrutinized for their potential to address conventional processing challenges. These techniques significantly enhance food safety and quality while minimizing environmental footprints. We explore recent progress and industrial applications indicating their effectiveness in extending shelf life, preserving nutritional values, and reducing resource consumption. The societal inferences, safety attention, regulatory issues, and consumer acceptance of these technologies are also discussed, highlighting the health rewards and the necessity for increased awareness and education. The review stresses nonthermal processing's pivotal role in promoting sustainable food systems by mitigating food waste, conserving resources, and lowering carbon emissions. It concludes with a call for current research and alliance to fully realize the potential of nonthermal technologies in securing a sustainable future for food production and consumption.